Los imperfectos de subjuntivo y la reestructuración del sistema verbal español afínales del siglo de oro - Luquet, Gilles (Studia Romanica Posnaniensia, 2004)
A historical analysis of the Spanish verb shows that the transition between the classical system and the modern system is characterized by two disappearances: the future subjunctive and the contrast between cantara and cantase. The present paper aims to show that: 1) abandoning the use of the future subjunctive has led directly to abandoning the contrast between cantara and cantase; 2) by the end of the classical period cantara was a form which was "programmed" to replace cantase; 3) in the modern and contemporary verbal system, cantara remains the same as in the classical system. Even if its referential capacities have somewhat altered, it remains the same single linguistic sign. This paper is based on a modal theory which differs the traditional contrast between indicative an subjunctive.